Principles of Modern Radar Missile Seekers - Markin, Evgeny (Artech House, 2022)
This book gives you an in-depth look into the critical function of interference shielding for onboard radar of anti-aircraft missile systems. Intended for radar engineers and technicians specializing in anti-aircraft defense, the book reviews today's military and geo-political threats, helps you understand the functional needs of the various radar and anti-missile systems to meet those threats, and synthesizes considerations for devising practical and effective protection against interferences that affect the homing heads of anti-aircraft guided missiles. Three problematic interferences are presented and discussed in detail: polarization interference; interference to the sidelobe of onboard antennas; and interference from two points in space, including interference reflected from the earth (water) surface. The book covers the basic principles of radiolocation, including monopulse radars, and gives insight into the fundamental functional units of anti-aircraft missiles and surface-to-air missile systems. The book presents guidance methods, systems of direction finding, problems on firing over the horizon, and questions of accuracy and resolution - all important for better addressing solutions of interference shielding.